Fabrication of CdS hierarchical multi-cavity hollow particles for efficient visible light CO₂ reduction - Zhang, Peng (2021)
Designing advanced structures for semiconductor photocatalysts is an effective approach to enhance their performance. However, it is not easy to fabricate functional photocatalytic materials with complex nano-architectures. Here we have developed a sequential solution growth, sulfidation and cation-exchange strategy to fabricate CdS hierarchical multi-cavity hollow particles (HMCHPs). This strategy starts with the growth of Zn-based zeolitic imidazolate framework (ZIF-8) onto cobalt glycerate (Co-G) solid spheres. Sulfidation of the obtained Co-G@ZIF-8 composite particles leads to the formation of CoSₓ@ZnS HMCHPs, which are converted into CdS HMCHPs via a cation-exchange reaction. Owing to the favourable properties of the well-defined hierarchical hollow structure, the CdS HMCHPs exhibit enhanced activity for photocatalytic CO₂ reduction compared with other CdS photocatalysts with solid and common hollow structures. The performance of CdS HMCHPs can be further promoted by loading of Au to reach a CO generation rate of 3758 μmol h⁻¹ g⁻¹ under visible light irradiation.